Strange particle production in relativistic nucleus-nucleus collisions in the RHIC BES energy region - 张聪聪 袁显宝 冯笙琴 殷中宝 (Chinese physics C, 2016)
The parton and hadron cascade model PACIAE is used to investigate strange particle production in Au ＋ Au collisions at √s = 62.4 GeV in different centralities and at √s =39, 11.5 and 7.7 GeV in the most central collision, respectively. It is shown that the transverse momentum distributions of strange particles by the PACIAE model fit the RHIC Beam Energy Scan experimental results well.